Bright shining : how grace changes everything - Baird, Julia (Julia Woodlands) (HarperOne, 2024)
"Grace is both mysterious and hard to define. It can be found when we create ways to find meaning and dignity in connection with each other, building on our shared humanity, being kinder, bigger, better with each other. If, in its crudest interpretation, karma is getting what you deserve, then grace is the opposite: forgiving the unforgivable, favouring the undeserving, loving the unlovable. But we live in an era when grace is an increasingly rare currency. The silos in which we consume information dot the media landscape like skyscrapers, and our growing distrust of the media, politicians and public figures has choked our ability to cut each other slack, to allow each other to stumble, to forgive one another. So what does grace look like in our world, and how do we recognise it, nurture it in ourselves and express it, even in the darkest of times? From award-winning journalist Julia Baird, author of the acclaimed national bestseller Phosphorescence, comes Bright Shining, a luminously beautiful, deeply insightful and most timely exploration of grace"--Publisher's description.